What influences uptake of psychosocial interventions by people living with early dementia? A qualitative study. (November 2021) - Field, Becky; Coates, Elizabeth; Mountain, Gail
Background: Health policy promotes post-diagnostic support for people affected by dementia. Evidence suggests psychosocial interventions can effectively support people living with dementia after diagnosis. Yet, what influences uptake of psychosocial interventions by people with early dementia is poorly understood. This research aimed to identify influences on uptake of psychosocial interventions by people with early dementia. Methods: Sixteen face-to-face semi-structured interviews with people with early dementia, either alone or with a family member(s), were completed. Twelve staff participated in semi-structured interviews or a focus group. Thematic analysis and triangulation enabled identification of overall themes across different participant groups and interview types. Main Findings: Four overarching themes influencing uptake were identified: (1) adjusting to a diagnosis, (2) appeal of activities and perception of benefit, (3) service and societal context, and (4) relationships and communication. Individual responses to diagnosis, experiences of dementia and dementia services influenced uptake. Group interventions were discussed the most by all participants. Group interventions offering social contact, peer support, information, enjoyable activities and mental stimulation were valued. However, group interventions specifically aimed at people with dementia did not appeal to all. Ability to travel and convenience of locations were important. Continuing with community activities not focused on dementia was valued. Stigma around dementia appeared to discourage uptake. Emotional and practical support from family was key to facilitating uptake as were the relationships between people with dementia and staff. Conclusion: A complex interplay of individual, service and societal influences affect uptake of psychosocial interventions by people with early dementia. How interventions and which services can enable people with early dementia remain engaged in their everyday lives needs consideration. Further research examining uptake of specific interventions commonly offered to people living with early dementia is needed. Involving people with early dementia in designing interventions aiming to support them is paramount.